Tinjauan Hukum Perdata Terhadap Akibat dan Penyelesaian Sengketa Usaha - Muhammad Luthfi De Vitra; Robbiah Nurul Hidayati; Najwatillah Khairani; Widia Keisya Octavianda; Muthia Maghfira; Helfira Citra (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
The purpose of this study is to analyze the legal consequences of default in business agreements and the mechanisms for settling business disputes. Default occurs when a party fails to fulfill their contractual obligations. This research uses a case study approach, specifically the decision of the Bengkulu District Court No. 17/Pdt.G/2025/PN Bgl regarding an insurance claim dispute. The results show that the insurer's refusal to pay a claim without adequate proof is categorized as an unlawful act. The court ordered the defendant to pay material damages of IDR 200,000,000. This study concludes that transparency and good faith are essential in maintaining legal certainty in business.